Dietary interventions in north Karelia, Finland and south Italy. Modification of thromboxane B2 formation in platelets of male subjects only - E. Tremoli; A. Petroni; S. Colli; R. Paoletti; C. Galli; A. Socini; P. Maderna; A. Ferro Luzzi; P. Strazzullo; M. Mancini (Atherosclerosis, 1986)
The effects of dietary interventions, based on changes of total fat, saturated fatty acids and cholesterol contents and of the polyunsaturated/saturated (P/S) fatty acid ratio of the diet, were studied in normal male and female subjects, living in North Karelia, Finland, and South Italy. In North Karelia the increase of P/S ratio (from 0.15 to 1.2) of the diet for a 6-week period resulted in reduced thromboxane B2 (TxB2) production by collagen-stimulated platelets only in male subjects, whereas plasma total, LDL and HDL cholesterol were reduced in both sexes. After a 6-week return to the original diet, plasma lipid levels were restored in all subjects. In the South Italy study, changes in platelet TxB2 production were observed only after return to the original diet in male subjects. Total and LDL cholesterol were significantly increased during the dietary intervention and returned toward baseline levels after switch back to the original diet. These data indicate that the increase of the P/S ratio in the diet reduces platelet TxB2 formation only in men.